Protes masyarakat Muslim Melayu-Patani Sebagai Upaya Memperoleh Hak Otonomi, 1902-1948 - Anas Fajarul, Ahmad (Qurthuba: The Journal of History and Islamic Civilization, 2024)
The purpose of this study is to analyze; how the social and political conditions of Malay-Patani Muslims in 1902? how the Malay-Patani Muslim protest movement in an effort to gain autonomy? and why the protest movement influenced the socio-political changes of Malay Muslims in Thailand? This research uses historical methods through the stages of heuristic, verification (source criticism), interpretation, and historiography. The results of this study show that 1) The defeat of Patani led by Tengku Abdul Kadir, made Patani and the surrounding Islamic areas have to submit to the Siamese kingdom so that they do not have autonomy both from politics, culture, language and religion; 2) There were protest movements aimed at fighting for the autonomy of Malay Muslims in Patani from 1910 to 1923, for example in 1910 and 1911 and the peak in 1921 to 1923 which was marked by the enactment of an education law aimed at eliminating Islamic educational institutions in Southern Thailand; 3) The issue of autonomy in Southern Thailand only reached a certain realm, and the Thai government basically issued these policies as a control over Malay Muslims so that they do not separate from Thailand. However, the mistake will be to understand from the aspirations conveyed by Malay Muslims that continue to give birth to protest movements until the future.